Art as a possible space for professional intervention of Social Work in the field of Mental Health - Bovino, Betina Mariel (Facultad de Ciencias Políticas y Sociales, 2021)
When we refer to the "field" of art or mental health, we refer to the conceptual notion of field as the meeting space between the two cores of knowledge, a place where things merge and mix and, in general, where the change occurs. Artwork in the field of mental health is not new. In this article we seek to explore the encounter between art and Social Work intervention strategies in the specific universo of mental health, a health area where this type of approach is becoming more and more common. We choose to carry out an analysis that combines the experience of empirical work with conceptual theoretical analysis. This work arises from the field research carried out by the author during the process of preparing her Doctoral Thesis in Social Work.